2021
DOI: 10.1080/26395940.2021.1960199
|View full text |Cite
|
Sign up to set email alerts
|

Effective adsorption of crystal violet from aqueous solutions with effective adsorbent: equilibrium, mechanism studies and modeling analysis

Abstract: In this work, NaOH-activated Aerva javanica leaf (NAJL) powder was successfully developed as a cost-effective adsorbent for removal of crystal violet (CV) from an aqueous environment. The prepared adsorbent was characterized using FTIR, SEM, and their surface area was determined by BET technique. Different parameters affecting the adsorption of CV dye such as pH solution, adsorbent dose, equilibrium time, initial CV concentration, and temperature were investigated. The results revealed that the best-optimized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(7 citation statements)
references
References 65 publications
3
3
1
Order By: Relevance
“…These results specify that it is preferable to operate this adsorption process at room temperature, which is economical and positively affects the adsorption process. This behavior is consistent with another study investigated by Al-Shehri et al [ 32 ].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…These results specify that it is preferable to operate this adsorption process at room temperature, which is economical and positively affects the adsorption process. This behavior is consistent with another study investigated by Al-Shehri et al [ 32 ].…”
Section: Resultssupporting
confidence: 94%
“…These results specify that it is preferable to operate this adsorption process at room temperature, which is economical and positively affects the adsorption process. This behavior is consistent with another study investigated by Al-Shehri et al [32]. The effect of temperature on the CV dye sorption on LCF was studied at various temperatures: 25, 40, 50, 60, and 70 °C.…”
Section: Effect Of Initial Dye Concentration and Isotherm Modelssupporting
confidence: 91%
“…Homidzadeh et al 37 proposed to use about 10 mg of magnetically modified activated carbon. Other studies showed the CV treatments with 10 mg of EDTA-GO/corncob, 13 20 mg of NaOHactivated Aerva javanica leaf powder, 44 25 mg of cellulosebased adsorbent (CGS), 20 45 mg of magnetic NaY zeolite, 22 or even 0.25 g of date palm fiber to achieve effectiveness at the same level like the results presented in this work. 45 Figure 5 shows the UV−vis spectra associated with the CV and CR dye adsorption measurements as a function of contact time.…”
Section: Dye Adsorptionsupporting
confidence: 75%
“…It was perceived that when the temperature rises, the adsorption capacity decreased marginally, indicating that the CR dye adsorption was an exothermic process. At higher temperatures, the binding forces on the surface with the CS-HAP-CeO 2 heterostructure adsorbent were destroyed [ 50 ]. These results were consistent to that of CR adsorption on a fly ash/CeO 2 composite adsorbent [ 51 ], malachite green and CR were removed from aqueous solution using magnetic HAP nanopowder [ 52 ], CR adsorption on graphene oxide/chitosan fibers [ 53 ], as well as CR adsorption on calcium HAP nanoparticles [ 54 ].…”
Section: Resultsmentioning
confidence: 99%